Large bowel obstruction due to splenic flexure volvulus: a case report - Adhikari, Shankar; Thapa, Bikas; Maharjan, Narendra; Ghimire, Bikal; Singh, Yogendra Prasad (Journal of Society of Surgeons of Nepal, 2019)
Splenic flexure volvulus is rare and results from congenital or postoperative laxity of splenic attachments. A 34 year old female presented with features of large bowel obstruction due to splenic flexure volvulus. She underwent laparotomy with detorsion and colopexy of the volvulus.